Bi-Ag as an alternative high temperature solder - Rosilli, Rohaizuan; Mohamed Ariff, Azmah Hanim; Muhamad Zam, Shahrul Fadzli (Universiti Putra Malaysia Press, 2014)
The search for a high temperature lead-free solder replacement for high temperature leaded solder eutectic alloy has been an evolving process as the threat of a regional lead ban became a reality in July 2006. The advantages and disadvantages of lead-free solder in terms of manufacturing, performance and reliability have been increasingly revealed through companies' Research and Development (R&D), industrial consortia and university researchers. Materials and component design are the primary criteria to focus on the development for the current generation of high temperature lead-free solder alloys. According to the current status of high temperature lead free soldering, there are many unsolved technical problems such as explanation on the lift-off phenomenon, establishment of high temperature lead-free plating technology, construction of a database of physical properties (solder, parts, PCBs), standardization of high temperature solder materials evaluation technology, and most importantly, the best candidate material for high temperature solder. Clearly, high temperature soldering is one of the unsolved problems of the century in lead-free soldering. Moreover, most of the questions still remain unanswered by researchers. This paper reviews research conducted on the Bi-Ag solder alloy, which is one of the candidate alloys that has been proposed as an alternative for high temperature lead-free solder.